PREMATURITAS SEBAGAI FAKTOR RISIKO GANGGUAN FUNGSI SEL RAMBUT LUAR KOKLEA - , Gerry Raymond Joviolo; , Dr. Kartono Sudarman, Sp.THT-KL(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Neonatus hearing impairment have the potential handicap in later social life, such as speech, language, cognitive and social function. Prematurity is one of several factors of hearing impairment due to immaturity of anatomic structure of the cochlea and also due to the immaturity of lung function in premature newborn. DPOAE is used as an objective tool to examined cochlea function by analyzing the function of cochlear outer hair cell. Objective: The aim of this research is to know the role of prematurity in cochlear outer hair cell dysfunction. Methods: Research design was case control study. Subjects of the research were neonates in NICU ward of Dr. Sardjito Hospital whom underwent DPOAE examination. Newborn with âReferâ result assigned as case population where as âPassâ result as the control population. Case and control population who qualified for the inclusion and exclusion criteria where used as sample. We employed chi square test, Mann-whitney test and logistic regression for statistical analysis. Result: There was no statistical difference on DPOAE result between the premature and non premature newborn. Nineteen (30,6%) of neonates that was born <32 weeks showed âReferâ result, and 59 (95,2%) of neonates born â¥32 weeks exhibited âPassâ result (p=0,0001(CI95% 2,41-31,23)). Conclusion: Prematurity was proven to be one of the risk factor for the dysfunction of cochlear outer hair cell on neonates born <32 weeks, but not for neonate born â¥32 weeks.